Wonder Woman’s Costume as a Site for Feminist Debate - Marcus, Jaclyn (Imaginations, 2018)
In this article, I examine how much of the fierce debate and discourse around Wonder Woman has centred around her costume. While several academics have addressed the relationship between Wonder Woman and feminism, my article engages with these works to examine the arguments surrounding Wonder Woman’s dress, particularly in the context of comic books and graphic novels that feature the character. The article argues that it is Wonder Woman’s apparel, and not her status as a superhero, that is the site of the controversy surrounding her persona and role as a feminist figure.